Komunikasi Efektif Dalam Meningkatkan Kualitas Hubungan Interpersonal di Lingkungan Kelas BPI 4B UIN Jakarta - N, Nasichah; Indriani, Yundari; Fatah, Fauzan Nurul; Putri, Amanda Tiara (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This life is not spared from communication, every human being must communicate in his daily life. The role of effective and good communication will build good communication quality. Interpersonal relationships are interpersonal relationships with each other.  The more active a person is in building relationships with others, the more extensive interpersonal networks will be built and produce quality self-competence. This is what can bring success in many ways. This journal aims to analyze the role of effective communication in building and improving interpersonal quality relationships, as explained above that interpersonal relationships are very important in life, therefore it is necessary to play an effective communication role in building them.